Dietary intake of live microbes mitigates the mortality risk associated with sedentary behavior in US hypertensive individuals - Xuanchun Huang; Lanshuo Hu; Jun Li; Chao Meng; Xiao Xia; Yiying Liu (Scientific Reports)
Abstract To investigate the association between dietary microbes intake and sedentary behavior with mortality risk in hypertensive adults in the United States. This study uses data from hypertensive individuals included in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. The relationship between live-microbe intake, sedentary time, and mortality risk among hypertensive individuals is preliminarily explored using Kaplan–Meier curves. Cox proportional hazards models are employed to analyze the associations separately and jointly, followed by subgroup analyses and sensitivity analysis to assess model stability. The study enrolled 10,036 participants with hypertension, among whom 1599 deaths occurred, including 512 cardiovascular disease-related deaths. Initial Kaplan–Meier curve analysis revealed that hypertensive individuals with both low intake of dietary live microbes and prolonged sedentary time had significantly higher mortality risk. Subsequent Cox proportional hazards model analysis demonstrated that high dietary microbial intake combined with reduced sedentary time were associated with lower mortality risk in hypertensive patients. Joint effect analysis suggested that maintaining proper dietary microbial eating habit may mitigate the adverse health effects of chronic sedentary behavior in this population. Subgroup and sensitivity analyses confirmed the stability of these findings across most examined conditions. The mortality risk in hypertensive individuals due to low intake of dietary live microbes and prolonged sedentary behavior is cumulative. Consuming foods rich in dietary microbes may help reduce the mortality risk associated with sedentary behavior in hypertensive populations.